Bibliometric analysis of the Doctor of Nursing Practice dissertations in the ProQuest Dissertations and Theses database - Shi, Xiuxiu; Zhou, Ying; Li, Zheng (Journal of advanced nursing, 2022)
Aims To examine the distributed characteristics and explore the research themes of Doctor of Nursing Practice (DNP) dissertations during the past two decades. Design A descriptive statistical and visualization bibliometric analysis was conducted. Methods Doctor of Nursing Practice dissertations submitted between January 2005 and June 2021 were collected from the ProQuest Dissertations and Theses database. A descriptive statistical analysis was conducted to calculate the distribution of the DNP dissertations by granting institution and the published year of publications. The VOSviewer 1.6.13 was used to explore the bibliometric networks and research priorities of the DNP dissertations. Results A total of 4989 DNP dissertations from 90 universities were included in this study, all from the United States. The number of DNP dissertations showed an upward trend, with steady growth from 2005 to 2014 and rapid growth after 2015. The DNP studies focused on five areas: health care management in clinical nursing, advanced practice in nursing education and health education, public health problems, mental health care for adolescents and nurses and the older people care and long‐term care. Conclusion Parallel to the numerical increase in DNP dissertations is a steady expansion in the range of research topics and scopes, which is aligned with specific specializations of the DNP. Many are interdisciplinary and employ techniques imported from the fields of public health, psychology and social sciences, resulting in nursing educators and practitioners continually broaden their subject perspectives. Impact Knowing where, when and why DNP research trends developed will help nursing educators to further develop DNP education and optimize DNP programs in the future, such as paying more attention to the nursing practice. Moreover, this study will inspire DNP students and researchers to expand their subject perspectives and broaden the research scope to solve nursing practice problems based on interdisciplinary theories and methods.